Closed and High-Quality Bacterial Genome Sequences of the Oligo-Mouse-Microbiota Community - Lamy-Besnier, Quentin (Microbiol Resour Announc, 2021)
The Oligo-Mouse-Microbiota (OMM(12)) gnotobiotic murine model is an increasingly popular model in microbiota studies. However, following Illumina and PacBio sequencing, the genomes of the 12 strains could not be closed. Here, we used genomic chromosome conformation capture (Hi-C) data to reorganize, close, and improve the quality of these 12 genomes.